2008
DOI: 10.1038/sj.ijo.0803799
|View full text |Cite
|
Sign up to set email alerts
|

Variability in adherence to an unsupervised exercise prescription in obese women

Abstract: Objective: To measure adherence to a specific exercise prescription (1500 kcal week À1 ) by objectively quantifying unsupervised exercise energy expenditure (ExEE) in obese women. Design: The 16-week lifestyle intervention consisted of weekly meetings with research staff and promotion of increased ExEE (1500 kcal week À1 ) and a decreased dietary intake (À500 kcal day À1 ). Participants: Twenty-nine obese females (body mass index ¼ 36.8 ± 5.0 kg m À2 , body fat ¼ 49.6 ± 3.7%) from a hospital-based lifestyle in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 37 publications
0
32
0
1
Order By: Relevance
“…Such methods are effective to reinforce adherence, but it was assumed that there was a danger of increasing the burden on caregivers by adding too much mental stress originally [8,9,13]. Furthermore, another study has reported that adherence to an unsupervised exercise regimen in obese women was poor [25]. However, supervision of female caregivers is a practical difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…Such methods are effective to reinforce adherence, but it was assumed that there was a danger of increasing the burden on caregivers by adding too much mental stress originally [8,9,13]. Furthermore, another study has reported that adherence to an unsupervised exercise regimen in obese women was poor [25]. However, supervision of female caregivers is a practical difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…Body composition was determined by dual energy X-ray absorptiometry (Lunar DPX, Lunar, Madison, WI) 23 and from measurements of total body water using the stable, nonradioactive, non-toxic isotope deuterium ( 2 H 2 O), as previously published. 24 Resting metabolic rate RMR was measured using a ventilated hood system (Deltatrac II, Datex, Helsinki, Finland) calibrated before each measurement with standardised gases.…”
Section: Anthropometry and Body Compositionmentioning
confidence: 99%
“…This suggests that studies investigating exercise-induced compensatory mechanisms should focus on individual variability rather than consider body fat or body weight changes in the group as a whole. In addition, such studies should ensure adherence to prescription of exercise since variability in the effectiveness of exercise in relation to body fat loss could be accounted for difference in compliance (8,10).…”
Section: Introductionmentioning
confidence: 99%